Evaluating Switchgrass (Panicum virgatum L.) as a Feedstock for Methane Production in Northern Europe - Eglė Norkevičienė; Kęstutis Venslauskas; Kęstutis Navickas; Carlo Greco; Kristina Amalevičiūtė-Volungė; Vilma Kemešytė; Aurelija Liatukienė; Giedrius Petrauskas; Bronislava Butkutė (Agriculture, 2025)
Interest in using warm-season grasses, including switchgrass (SG) (Panicum virgatum L.), as a bioenergy crop has increased in Europe. This study evaluated the effects of harvesting regimes with two cuts per year on the productivity, chemical composition and biochemical methane potential of the SG cultivars ‘Dacotah’, ‘Foresburg’ and ‘Cave in Rock’ in environments with cool and moderate climates in Europe with minimal fertilizer application. The results of two harvest years suggest that the biomass yield, chemical composition and energy potential depend on the grass cultivars and harvesting time. Significant effects (p < 0.05) of the harvest date and cultivar were observed for most of the measured parameters for biomass and silage quality. All three SG cultivars harvested on August 8 produced the lowest (p < 0.05) volume of methane per kg of biomass (181–202 normal litres (NL) per kg−1 volatile solids (VS)) compared to the biomass of the respective cultivar harvested on 14 July (287–308 NL kg−1 VS) or on October 3, as regrowth after the first cut made in mid-July (274–307 NL kg−1 VS). The stands of all three SG cultivars, when the first harvest was completed in mid-July, achieved a higher annual area-specific methane yield than those harvested first in August (1128–1900 Nm3 ha−1 and 888–1332 Nm3 ha−1, respectively). Depending on the harvest regime and cultivar, the annual gross energy presented as a lower heating value varied from 31.8 GJ ha−1 to 68.0 GJ ha−1. It is concluded that SG growing under the cool temperate climate of Northern Europe could be an interesting alternative crop for methane production. Our study proves that the cultivar choice also plays an important role.